Stability of Trinitroglycerin in Polyethylene Glycol 400: Stability of TNG in PEG 400 - Shamsa, Fazel (Iranian Journal of Pharmaceutical Sciences, 2005)
In this study, the stability of trinitroglycerin (TNG) in polyethylene (PEG) 400 was investigated according to Arrhenius approach. The reaction rate constant (k) for the thermal disintegration of TNG in PEG 400 at various temperatures was counted based on the percents of remaining TNG at different intervals of time at a specific temperature. The results showed that “k” at 40, 50, 60, 70, 80 and 90 ºC were 6.5x10- 4, 3.57x1 0- 3, 4.7x1 0- 3, 3x1 0- 2, 6.2x10- 2 and 6.5x1 0- 2, respectively. By plotting “log k” against temperature (1/T), “k” was obtained at 5 and 20 oC which was 1.47x10- 5 and 7.94x10-5, respectively. The results showed the time required to attend 90, 80, 70, and 50 percent of the original TNG at 5 oC was 9.76, 20.7, 33, and 64.2 months, respectively. The results assist in the calculation of the expiration time of TNG/ PEG 400.